2020
DOI: 10.1186/s12917-020-02640-9
|View full text |Cite
|
Sign up to set email alerts
|

Solitary tracheal B-cell lymphoma in an adult alpaca (Vicugna pacos)

Abstract: Background This report describes a case of solitary tracheal lymphoma in a 14-year-old alpaca mare. Case presentation The alpaca was referred for dyspnea and inspiratory noise. The clinical examination included complete blood cell count, blood chemistry, endoscopy, ultrasound, radiographs, and computed tomography (CT). A solitary tracheal intraluminal and juxtatracheal lymphoma was diagnosed by fine needle aspiration (FNA). The owner requested euthanasia due to the uncertain prognosis. At postmortem examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Descriptions of the use of prednisolone in the camelid medical literature are sparse. Historical reports describe prednisolone for chemotherapy of lymphosarcoma or lymphoma (23,24). Anti-inflammatory doses are used for management of soft tissue injury from causes such as cerebrospinal nematodiasis and rattlesnake envenomation (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptions of the use of prednisolone in the camelid medical literature are sparse. Historical reports describe prednisolone for chemotherapy of lymphosarcoma or lymphoma (23,24). Anti-inflammatory doses are used for management of soft tissue injury from causes such as cerebrospinal nematodiasis and rattlesnake envenomation (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Future directions for prednisonolone in alpacas include pharmacodynamic studies. One key area for further pharmacodynamic investigation is the use of prednisolone for anti-neoplastic therapy, considering the alpaca's role as a primarily companion animal, and the propensity of older alpacas to develop cancer (24,38,39). Additional research is needed to elucidate the effects that body condition could have on the pharmacokinetics of prednisolone in alpacas, as overconditioning (increased body fat percentage) in some species, such as cats, is associated with higher serum concentrations (40).…”
Section: Discussionmentioning
confidence: 99%
“…The report by Valentine et al reports only 12.5% of all neoplastic cases being lymphoma (5 out of 40 cases), and it was the third most common tumor following fibromas/fibropapillomas/fibrosarcomas and squamous cell carcinomas (3). In the published cases, lymphoma generally presented widely disseminated with rare reports of cutaneous and solitary masses (5,43,59). Phenotyping by immunohistochemistry in 63 of these cases identified 24 B cell (38%), 28 T cell (44%), 1 mixed T and B cell, and 13 (20.6%) as non-B, non-T cell lymphoma (43,(48)(49)(50)(51)(52)(54)(55)(56)(57)(58)(59).…”
Section: Literature Casesmentioning
confidence: 99%
“…In the published cases, lymphoma generally presented widely disseminated with rare reports of cutaneous and solitary masses (5,43,59). Phenotyping by immunohistochemistry in 63 of these cases identified 24 B cell (38%), 28 T cell (44%), 1 mixed T and B cell, and 13 (20.6%) as non-B, non-T cell lymphoma (43,(48)(49)(50)(51)(52)(54)(55)(56)(57)(58)(59).…”
Section: Literature Casesmentioning
confidence: 99%
“…In literature, a difference in the age of alpacas (2 years of age and less) and llamas (5–7 years) is described suffering from lymphomas [ 1 , 4 , 7 10 ]. Marchionatti et al [ 11 ] reported a similar case of a solitary tracheal lymphoma in an adult alpaca. This alpacas was also referred for dyspnoea and inspiratory noise and a clinical examination, endoscopy, ultrasound, radiographs and computed tomography was performed.…”
Section: Introductionmentioning
confidence: 99%